OAUNI photometry of SN 2024ggi - Pereyra, Antonio (2024)
We report photometry of Type II SN 2024ggi gathered with the OAUNI 51cm telescope (arXiv:1512.03104) at Huancayo Observatory, Peru. CCD imaging in R filter was performed on five consecutive nights under nonˇphotometric conditions with airmasses lower than 1.6. The integration time was 50x20s=1000s in the first observation and 60x20s=1200s for the rest. Our measurements yielded: Date (UT) | filter | seeing (") | mag, 2024-06-05.108 | R | 3.2 | 12.27 +/- 0.06, 2024-06-06.080 | R | 2.6 | 12.25 +/- 0.06, 2024-06-07.064 | R | 2.8 | 12.27 +/- 0.06, 2024-06-08.061 | R | 2.7 | 12.27 +/- 0.06, 2024-06-09.062 | R | 2.9 | 12.28 +/- 0.06. UCAC4 field stars were used for the zero point calibration. Our observations are ~7.9 weeks after ATLAS discovery (TNSAN-2024-100). The OAUNI project is supported by UNI, TWAS, IGP and ProCiencia-Concytec (Convenio 133-2020 Fondecyt).